Development of Scientific Comprehension Assessment Instruments With Two-Tier Multiple Choice Assisted by Thunkable on the Topic of Work and Energy - Ravena Nawang Ara; Sukarmin Sukarmin (Jurnal Materi dan Pembelajaran Fisika, 2025)
This study aims to develop a instrument for assessing scientific comprehension with Two-Tier Multiple Choice Assisted by Thunkable on the Topic of Work and Energy that meets the criteria as a good assessment instrument. This study uses a development research method from the Wilson, Oriondo, and Antonio (1998) model, namely the test design stage which begins with determining the purpose of the test, determining the competencies tested, determining the material tested, preparing the test grid, writing items, validating items, improving items and assembling tests, and preparing scoring guidelines, then instrument validation carried out by determining the test subjects, conducting trials, and analyzing the data from the trial results and completing with a broad test measurement. The data collection method used was a questionnaire using a two-tier multiple choice instrument in the form of a thunkable-assisted application. The data sources were 6 experts and 270 students from 3 schools, namely SMA Negeri 1 Sukoharjo, SMA Negeri 1 Tawangsari, and SMA Negeri 1 Bulu. The results showed that of the 22 items of scientific comprehension assessment instruments with two-tier multiple choice assisted by thunkable on the topic of work and energy with the Quest program, 20 items were declared fit with the Rasch model. The conclusion of this research is that the instrument of scientific comprehension with two-tier multiple choice assisted by thunkable on the topic of work and energy as a good assessment instrument based on the Rasch model.